Genetic dissection of memory for associative and non‐associative learning in Caenorhabditis elegans. (1st November 2012) - Lau, H. L.; Timbers, T. A.; Mahmoud, R.; Rankin, C. H.
<x xml:space="preserve">Abstract</x> The distinction between non‐associative and associative forms of learning has historically been based on the behavioral training paradigm. Through discovering the molecular mechanisms that mediate learning, we can develop a deeper understanding of the relationships between different forms of learning. Here, we genetically dissect short‐ and long‐term memory for a non‐associative form of learning, habituation and an associative form of learning, context conditioning for habituation, in the nematode Caenorhabditis elegans. In short‐term chemosensory context conditioning for habituation, worms trained and tested in the presence of either a taste (sodium acetate) or smell (diacetyl) context cue show greater retention of habituation to tap stimuli when compared with animals trained and tested without a salient cue. Long‐term memory for olfactory context conditioning was observed 24 h after a training procedure that does not normally induce 24 h memory. Like long‐term habituation, this long‐term memory was dependent on the transcription factor cyclic AMP‐response element‐binding protein. Worms with mutations in glr‐1 [a non‐N‐methyl‐d‐aspartate (NMDA)‐type glutamate receptor subunit] showed short‐term but not long‐term habituation or short‐ or long‐term context conditioning. Worms with mutations in nmr‐1 (an NMDA‐receptor subunit) showed normal short‐ and long‐term memory for habituation but did not show either short‐ or long‐term context conditioning. Rescue of nmr‐1 in the RIM interneurons rescued short‐ and long‐term olfactory context conditioning leading to the hypothesis that these interneurons function to integrate information from chemosensory and mechanosensory systems for associative learning.